Crude Oil Prices and Economic Development in Libya - Aimer, Nagmi M. Moftah (Asian Economic and Social Society, 2016)
This paper aims to examine the effects of oil price shocks on the economical development in Libya? during the period 1968-2016, using annual data. A unit root test was conducted, in which the series was shown to be non-stationary in the level, and all variables became stationary in the first difference.. The co-integration model was applied, and the results indicated that there is a long-term relationship of oil prices on the economical development. Finally, this study concludes that increases in oil price did not significantly affect the manufacturing sector in aggregate terms. Moreover, the negative impact on the sector of agriculture Thus, this study has a significant impact in the Libyan economy in policy development on oil prices. The Libyan government needs to control the price to make sure that price volatility will not harm the manufacturing, agriculture and construction sectors.
Keywords: 8. Economic growth; 1. No poverty